2011
DOI: 10.1007/s00520-011-1255-0
|View full text |Cite
|
Sign up to set email alerts
|

Trends in anemia management in lung and colon cancer patients in the US Department of Veterans Affairs, 2002–2008

Abstract: Use of ESA treatment for anemia in VA cancer care declined markedly after 2005, well before the 2007 changes in product labeling and clinical guidelines. This suggests that earlier dissemination of research results had marked impacts on practice patterns with these agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 32 publications
5
12
0
Order By: Relevance
“…The Our results are consistent with prior studies showing decreases in ESA use [25][26][27][28][29][30] and increases in transfusion use 25,[27][28][29] following the ESA label change and subsequent NCD. Henry et al 27 showed that the number of ESA administrations per patient decreased from a mean of 4.6 to 2.9 following the NCD, nearly identical to our results.…”
Section: Discussionsupporting
confidence: 92%
“…The Our results are consistent with prior studies showing decreases in ESA use [25][26][27][28][29][30] and increases in transfusion use 25,[27][28][29] following the ESA label change and subsequent NCD. Henry et al 27 showed that the number of ESA administrations per patient decreased from a mean of 4.6 to 2.9 following the NCD, nearly identical to our results.…”
Section: Discussionsupporting
confidence: 92%
“…Insights from our study show the result of many potential causal changes in ESA use across a variety of insurance and patient types. A prior review of cancer patients with CIA identified decreased darbepoetin use following the 2006 Cochrane report of a 67% increase in VTE rate among patients who received an ESA 7 in Medicaid 16 and the Department of Veterans Affairs data 23 . Examination of the merged Surveillance Epidemiology and End Results‐Medicare databases attributed changes in ESA use for CIA to the 2007 Black Box warning, which occurred at a similar time to the decrease in darbepoetin use we report 15 .…”
Section: Discussionsupporting
confidence: 53%
“…A prior review of cancer patients with CIA identified decreased darbepoetin use following the 2006 Cochrane report of a 67% increase in VTE rate among patients who (a) ( c) received an ESA 7 in Medicaid 16 and the Department of Veterans Affairs data. 23 Examination of the merged Surveillance Epidemiology and End Results-Medicare databases attributed changes in ESA use for CIA to the 2007 Black Box warning, which occurred at a similar time to the decrease in darbepoetin use we report. 15 Analyses of Medicare data after the 2008 CMS decision restricting ESA use to cancer patients with hemoglobin levels less than 10 mg/dl showed increased risk of VTE.…”
Section: Resultsmentioning
confidence: 53%
“…Among VA cancer patients, ESA use plateaued in late 2003 and sharply declined from 38% (2006) to 12% (2008) among colon cancer patients and from 23% (2006) to 5% (2008) among lung cancer patients. 10 Another study of cancer patients undergoing chemotherapy across 39 sites in seven states reported a decline from 41% to 30% between 10-month intervals before and after the 2007 FDA black-box warning. 12 Two studies of cancer patients treated at MD Anderson Comprehensive Cancer Center reported decreases in ESA use between 2006 and 2008 of 17% to 5% and 4% to 1%.…”
Section: Discussionmentioning
confidence: 99%
“…1018 However, no information exists regarding trends in anemia treatment among patients with both ESRD and cancer.…”
Section: Introductionmentioning
confidence: 99%